A Public-Health-Based Vision for the Management and Regulation of Psychedelics. Issue 4 (7th August 2016) - Haden, Mark; Emerson, Brian; Tupper, Kenneth W.
ABSTRACT: The Health Officers Council of British Columbia has proposed post-prohibition regulatory models for currently illegal drugs based on public health principles, and this article continues this work by proposing a model for the regulation and management of psychedelics. This article outlines recent research on psychedelic substances and the key determinants of benefit and harm from their use. It then describes a public-health-based model for the regulation of psychedelics, which includes governance, supervision, set and setting controls, youth access, supply control, demand limitation, and evaluation.